Paradigm Education Islam in Transformation System Trust Traditional - M Hijaz Tahir; Sam Hermansyah (International Journal of Sustainable Applied Sciences, 2023)
Islamic education encourages generations to change and maximize potential himself in carry out his task as abid And caliph with flavor responsibility. A tough personality and a love of science born from outer education Islam, so community social will experience change to a better one based on the demands and needs of the times. Education Islam is a process of introducing authentic and kaffah Islam to people participant educate without as well as immediately negate culture And tradition local, precisely accommodate And justify wisdom local Which assessed in line with teachings Islam. Culture And tradition is results work man Which born from„ womb ‟ of history is considered sacred and respected by the human community. Education Islam is a holistic educational concept that accommodates all views a world that is 'bound' in Islamic monotheistic reasoning and emphasizes activities always dimensions transcendent in a way consistent And grow creativity in realizing the caliph's mission as the main task of making Islam a religion Rahmatan lil natural.